Contributions of Zootaxa to biodiversity discovery: an overview of the first twenty years - Zhang, Zhi-Qiang (Zootaxa, 2021)
On the 20th anniversary of Zootaxa, I herein provide an overview of its development and contributions over the last two decades (2001 to 2020) and an introduction to this special volume of 25 collected papers in celebration. Zootaxa published over 29,400 papers (including 1,499 monographs of 60 or more pages) by more than 28,000 authors in over 585,000 pages during these two decades. Zootaxa published 60,470 new species (subspecies), 272 new subgenera, 4,206 new genera, 26 new subtribes, 152 new tribes, 234 new subfamilies, 170 new families, nine new superfamilies, 41 new taxa (outside of the species, genus and family groups), and 996 new names in the past two decades. Since 2005, Zootaxa accounted for 26.6% of all new taxa/names indexed in Zoological Record. Zootaxa also published 12,684 new synonyms from 2001 to 2020. Zootaxa published papers for over 28,000 authors from 131 countries during the last two decades; about two-thirds of them published only one or two papers over the 20 years. The significant impacts of Zootaxa on advancing global taxonomy are discussed.